Reactive Oxygen Species and Their Consequences on the Structure and Function of Mammalian Spermatozoa - Drevet, Joël R; Hallak, Jorge; Nasr-Esfahani, Mohammad-Hossein; Aitken, Robert J (Antioxidants & redox signaling, 2022)
Among the 200 or so cell types that comprise mammals, spermatozoa have an ambiguous relationship with the reactive oxygen species (ROS) inherent in the consumption of oxygen that supports aerobic metabolism. In this review, we shall see that spermatozoa need the action of ROS to reach their structural and functional maturity, but that due to intrinsic unique characteristics, they are, perhaps more than any other cell type, susceptible to oxidative damage. Recent studies have improved our knowledge of how oxidative damage affects sperm structures and functions. The focus of this review will be on how genetic and epigenetic oxidative alterations to spermatozoa can have dramatic unintended consequences in terms of both the support and the suppression of sperm function. Oxidative stress can have dramatic consequences not only for the spermatozoon itself, but also, and above all, on its primary objective, which is to carry out fertilization and to ensure, in part, that the embryonic development program should lead to a healthy progeny. Sperm oxidative DNA damage largely affects the integrity of the paternal genetic material to such an extent that the oocyte may have difficulties in correcting it. Diagnostic and therapeutic actions should be considered more systematically, especially in men with difficulties to conceive. Research is underway to determine whether the epigenetic information carried by spermatozoa is also subject to changes mediated by pro-oxidative situations.